Harnessing Mosaic-Adjuvanted Nucleic Acid Nanovaccines for Enhanced Avian Influenza Immunity - Mr Bubacarr J. B Touray; Dr Fakry Ramadan; Dr Adel M Talaat (International Journal of Infectious Diseases)
Background: Avian influenza remains a significant threat to the global poultry industry and public health authorities, worldwide. Developing effective vaccination strategies for disease control in both poultry and humans would alleviate this important “One Health” concern. This study investigates the immunogenicity of mosaic hemagglutinin (mHA) DNA vaccines in chickens, with a focus on the impact of adjuvants and various administration routes on vaccine efficacy. Methods: Day-old chickens were subjected to two doses of 100 µg mHA DNA vaccine, administered either in naked form or adjuvanted with Quil-A and Chitosan (QAC) or Quil-A and DOTAP (QTAP). Different administration routes were utilized, with a 2-week interval between doses. The study spanned 35 days, culminating in euthanasia for comprehensive analysis. Immune responses were evaluated through hemagglutination inhibition (HI) titers against multiple H5 serotypes, serum immunoglobulin G (IgG) levels, and immunoglobulin A (IgA) levels in tears. Results: The study demonstrated consistent chicken body weight throughout the experimental period, indicating the safety of the employed vaccination protocols. Notably, a single subcutaneous (SQ) dose of QTAP-mHA vaccine elicited significantly elevated HI titers compared to other vaccination groups. Moreover, both SQ/ON (subcutaneous/oculo-nasal) and SQ/SQ administration routes of QTAP-mHA induced heightened levels of serum IgG and tear IgA, highlighting the adaptability of the vaccine and delivery methods in stimulating systemic and mucosal immune responses. Discussion: The findings underscore the potential immunogenicity of mHA DNA vaccines in chickens, with adjuvants and administration routes playing crucial roles in enhancing immunogenicity. The observed safety profile, coupled with superior immune responses, supports further testing of vaccine efficacy in challenge models. Comparisons with existing studies suggest promising prospects for broadening the application of mHA DNA vaccines in poultry and other models suitable to mimic human infections (e.g. ferrets). Also, further research is warranted to evaluate vaccine performance under field conditions and its impact on reducing disease transmission. Conclusion: In conclusion, this study elucidates the promising immunogenicity of mosaic hemagglutinin (mHA) DNA vaccines in chickens, with adjuvants and diverse administration routes significantly enhancing vaccine efficacy. The absence of adverse effects on chicken body weight, combined with superior immune responses, validates the effectiveness of this vaccination strategy against avian influenza. Future research endeavors should focus on evaluating the vaccine's performance under real-world conditions and assessing its potential in mitigating disease spread within animal and human populations.